(untitled) (The Pakistan Development Review, 1986)
It is fashionable in some intellectual circles to deride the trickle-down theory, technological change, and the Green Revolution as tools of the haves to exploit the have-nots. In a worthwhile book, drawing especially on extensive data for India, several distinguished analysts from various countries examined sources of rural poverty with special attention to the role of technological progress and the trickledown theory.